2011
DOI: 10.1002/fam.1082
|View full text |Cite
|
Sign up to set email alerts
|

A novel halogen‐free and formaldehyde‐free flame retardant for cotton fabrics

Abstract: SUMMARYA novel halogen-free and formaldehyde-free flame retardant (FR), which contains phosphorus, nitrogen, and silicon, was synthesized for cotton fabrics considering the synergistic effect of phosphorus, nitrogen, and silicon. The structure of the new FR was characterized by Fourier-trans-form infrared spectroscopy, and the surface morphology of the treated fibre was observed using scanning electron microscope. The thermal property of the FR treated cotton fabric was studied through thermal gravimetric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 16 publications
0
26
0
4
Order By: Relevance
“…Product (39) promoted char formation and decreased the THR of the treated samples with increases in the add-on on the treated fabrics. On the other hand, vertical flammability tests performed on cotton fabrics treated with (39) showed an increase after flame and no afterglow phenomena [52].…”
Section: Phosphoramidate Flame Retardantsmentioning
confidence: 91%
See 4 more Smart Citations
“…Product (39) promoted char formation and decreased the THR of the treated samples with increases in the add-on on the treated fabrics. On the other hand, vertical flammability tests performed on cotton fabrics treated with (39) showed an increase after flame and no afterglow phenomena [52].…”
Section: Phosphoramidate Flame Retardantsmentioning
confidence: 91%
“…From an overall point of view, it was found that the flame retardant performance of the fabrics treated with 39 was much better than that of the substrates treated with same add-on of (42). Furthermore, when cotton fabrics were treated with (39) and (43), they showed almost the same FR performances. The products were applied onto cotton fabrics from acetone solutions with different concentrations of phosphoramidates (36)- (41).…”
Section: Phosphoramidate Flame Retardantsmentioning
confidence: 98%
See 3 more Smart Citations